Diskursus Toleransi Agama dalam Podcast #LogIndiCloseTheDoor - Manahara Alamsyah Lubis (Jurnal Komunikasi Islam, 2024)
Social media offers a new space for disseminating ideas about religious tolerance. Efforts to suppress the spread of religious-based radicalism and intolerance have been carried out by various state institutions, organizations, religious figures, and influencers in the digital space. One of the digital media that is quite popular in spreading the idea of religious tolerance lately is the #LogIndiCloseTheDoor podcast initiated by Deddy Corbuzier and hosted by Habib Ja'far. This study focuses on the message of tolerance in the #LogIndiCloseTheDoor podcast. Using the library research method, the results of this study illustrate that the messages of tolerance contained in this channel are found in episodes 18, 26, and 28. In these episodes, several messages of religious tolerance suit the principles of tolerance taught by Islam, namely al-hurriyah al-diniyah and al-insaniyyah.